Impact of Regulatory Guidance on Evaluating Cardiovascular Risk of New Glucose-Lowering Therapies to Treat Type 2 Diabetes Mellitus: Lessons Learned and Future Directions. Issue 10 (10th March 2020) - Sharma, Abhinav; Pagidipati, Neha J.; Califf, Robert M.; McGuire, Darren K.; Green, Jennifer B.; Demets, Dave; George, Jyothis Thomas; Gerstein, Hertzel C.; Hobbs, Todd; Holman, Rury R.; Lawson, Francesca C.; Leiter, Lawrence A.; et al.
Abstract : Responding to concerns about the potential for increased risk of adverse cardiovascular outcomes, specifically myocardial infarction, associated with certain glucose-lowering therapies, the US Food and Drug Administration and the Committee for Medicinal Products for Human Use of the European Medicines Agency issued guidance to the pharmaceutical industry in 2008. Glucose-lowering therapies were granted regulatory approval primarily from smaller studies that have demonstrated reductions in glycated hemoglobin concentration. Such studies were overall underpowered and of insufficient duration to show any effect on cardiovascular outcomes. The 2008 guidance aimed to ensure the cardiovascular safety of new glucose-lowering therapies to treat patients with type 2 diabetes mellitus. This resulted in a plethora of new cardiovascular outcome trials, most designed primarily as placebo-controlled noninferiority trials, but with many also powered for superiority. Several of these outcome trials demonstrated cardiovascular benefits of the newer agents, resulting in the first-ever cardiovascular protection indications for glucose-lowering therapies. Determining whether the guidance continues to have value in its current form is critically important as we move forward after the first decade of implementation. In February 2018, a think tank comprising representatives from academia, industry, and regulatory agencies convened to consider the guidance in light of the findings of the completed cardiovascular outcome trials. The group made several recommendations for future regulatory guidance and for cardiovascular outcome trials of glucose-lowering therapies. These recommendations include requiring only the 1.3 noninferiority margin for regulatory approval, conducting trials for longer durations, considering studying glucose-lowering therapies as first-line management of type 2 diabetes mellitus, considering heart failure or kidney outcomes within the primary outcome, considering head-to-head active comparator trials, increasing the diversity of patients enrolled, evaluating strategies to streamline registries and the study of unselected populations, and identifying ways to improve translation of trial results to general practice.